Understanding the wage patterns of Canadian less skilled workers: The role of implicit contracts - David A. Green; James Townsend (Institute for Fiscal Studies (IFS), 2009)
We examine the wage patterns of Canadian less skilled male workers over the last quarter century by organizing workers into job entry cohorts. We find entry wages for successive cohorts declined until 1997, and then began to recover. Wage profiles steepened for cohorts entering after 1997, but not for cohorts entering in the 1980s - a period when start wages were relatively high. We argue that these patterns are consistent with a model of implicit contracts with recontracting in which a worker's current wage is determined by the best labour market conditions experienced during the current job spell.
Keywords: J31; O33; 330; Männliche Arbeitskräfte; Ungelernte Arbeitskräfte; Qualifikation; Lohnniveau; Lohnstruktur; Kanada